2023
DOI: 10.1109/access.2023.3249102
|View full text |Cite
|
Sign up to set email alerts
|

FDTD Investigation of Efficient and Robust Integration Between Si3N4 and Ge-Rich GeSi for Waveguide-Integrated Electro-Absorption Optical Modulators

Abstract: Si3N4 photonic integrated circuits have gain significant and rapid interest in different photonic applications thanks to its superior passive performance. Nevertheless, optical integration between Si3N4 and Ge-based optical components remains critically challenging especially for optical modulation. In this paper, via 3D-FDTD calculations we investigate the optical integration between Si3N4 and Ge-based waveguides using vertical coupling configuration employing amorphous Si (α-Si) as an optical bridge showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…41 In recent years, it has been demonstrated that high-performance photodetectors integrating waveguides can achieve detection in the ultraviolet (UV) to infrared (IR) region. [42][43][44] At present, the waveguide materials employed in the fabrication of photodetectors are mainly Si, Si 3 N 4 , GaN, lithium cyanate (LN), and ZnO, [45][46][47][48][49] which transmit IR, VIS, and UV light, respectively, due to their inherent properties. Since the first successful exfoliation of graphene in 2004, 50 two-dimensional (2D) semiconductor materials have attracted increasing attention in photoelectric detection due to their unique structure and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…41 In recent years, it has been demonstrated that high-performance photodetectors integrating waveguides can achieve detection in the ultraviolet (UV) to infrared (IR) region. [42][43][44] At present, the waveguide materials employed in the fabrication of photodetectors are mainly Si, Si 3 N 4 , GaN, lithium cyanate (LN), and ZnO, [45][46][47][48][49] which transmit IR, VIS, and UV light, respectively, due to their inherent properties. Since the first successful exfoliation of graphene in 2004, 50 two-dimensional (2D) semiconductor materials have attracted increasing attention in photoelectric detection due to their unique structure and physical properties.…”
Section: Introductionmentioning
confidence: 99%